Penerapan Metode Talaqi dalam Menghafal Al Qur’an di SDIT Iqro’ Gedongtataan - Ruly Nadian Sari; Sriwiyana Sriwiyana; Eka Setianingsih (Journal on Education, 2024)
It is not easy for a man to memorize the Qur'an unless he has the time, the effort and the ability to do it. But if it is done with a sincere intention, then it will yield maximum results. This research applies a qualitative approach using descriptive methods. The purpose of this study is to find out how to implement the talaqi method in memorizing the Qur’an by 30 students of the fourth grade Zubair bin Awwam at SDIT Iqro’ Gedongtataan. The results of this study show that, the application of the talaqi method in SDIT Iqro’ Gedongtataan in particular in the class IV Zubair bin Awwam has an impact on the quality of hafalan santri. This is because there are many students who experience increased awareness due to the talaqi method there is a significant interaction between ustadz/ustazah and students in teaching the Qur’an.